Creatividad en el proceso de enseñanza aprendizaje en los estudiantes de sexto año de educación básica de la escuela “Isabel La Católica” del cantón Babahoyo, provincia de Los Ríos - Abril Onofre, Segundo Geovanny (2019)
The intention of the present investigation is twofold: originally, to deliberate on the compendiums that establish the conceptualization of creativity and, then, to offer educators certain indications that help by providing their students with a moderate pressing in which the discovery of creative skills is benefited and its manifestation. Objective: To determine the contribution of creativity in the teaching-learning process in students in the sixth year of basic education at the "Isabel La Católica" school, in the Babahoyo canton. Methodology: Through observation, the lack of motivation towards the generation of areas where students' creativity is encouraged is evidenced. Results: That creativity be considered as a main mechanism in the progress of the teaching-learning processes in the students of the Isabel La Católica School. Conclusion: That creativity as an essential strategy in the development of the teaching-learning process of students is not sufficiently exploited in the classroom and in homes as a complement to education, so parents should be instructed to train Share and help your children in the development of creativity